(3GdHjQRIs
(3ChdgG (B:s
(3PcQ GdKbGJ ef GdQhGI Cgd GdeYQaI Cf GdCScfOQ GdQhej bGd ddMceGA(B: (3CQjO Cf JYQahfj HWHjYI GdHGRj hCeQGVg GdYGQVI dg, hYdGeI cd eQV s
(3BNQgG (B:s
(3aEPG YGO GdWjQ ef GdUjO jOQL dg aj WYeg efg TF aEfg jfaYg hjYWj Pdc aj GdTgQ OaYJjf aj MGd UMJg s
(3GdcJGH LRBf cd LRA YHGQI Yf ebGdIs
(3hgh oeQJH Ydi CHhGH LedJgG (B115 (3HGHkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B41 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs